Pelatihan Pembuatan Media Pembelajaran Game Interaktif Bagi Guru Madrasah Ibtidaiyah Miftahul Ulum Desa Kuantan Sako - Mualif, Ahmad; Haswan, Febri; Nopriandi, Helpi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Interactive learning media is one of the supporting components of learning activities to be more interactive and innovative, digital-based learning in the form of interactive games in the current era is very useful as a support for education, with the existence of interactive game learning media can stimulate children's interest in learning more quickly, therefore it is necessary to increase human resources for teachers of Madrasah Ibtidaiyah Miftahul Ulum Kuantan Sako Village to provide insight and understanding in building interactive games using wordwalls. The results of this community service activity are in the form of interactive learning media in the form of games in the form of quizzes, wordsearch, to anagrams, this game can later be used by students at Madrasah Ibtidaiyah Miftahul Ulum Kuantan Sako Village with the aim of improving learning in the classroom so that the learning process is not boring and becomes more enjoyable.